(untitled) (ASEAN Engineering Journal, 2015)
We present the security weakness of encryption algorithm in the form of substitution-permutation network with multiple rounds of permutation and single round of diffusion proposed by W. Zhang et al. The types of chosen-plaintext and chosen-ciphertext attacks are successful against the cryptosystem, and the equivalent versions of keys for encryption and decryption are restored. The security analysis suggests that encryption using substitution-permutation network must be executed more than one encryption round to ensure the security. Our specific examples will demonstrate the cryptanalysis.